TRANSFORMASI PERGURUAN TINGGI KEAGAMAAN ISLAM INDONESIA - Rio Hidayat; Wedra Aprison (CV. ADIBA AISHA AMIRA, 2025)
Higher education is not only a means of knowledge transformation but also a dynamizer of society. Islamic religious universities spread from Banda Aceh to Jayapura as well as a means of community development. Various forms of programs carried out in order to show a more technical form of Islamic moderation. Scientific development includes the opening of varied majors that give students the flexibility to learn science technically. This paper shows that Islamic religious universities also develop programs that do not focus on universities. However, at the same time, there are challenges that need to be overcome so that the development of Islamic religious higher education is not only in public institutions but also in the private sector.